2020
DOI: 10.26434/chemrxiv.13299785.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Bio-Inspired Lanthanum-Ortho Quinone Catalyst for Aerobic Oxidation of Alcohol

et al.

Abstract: <p>Oxidation reactions are fundamental transformations in organic synthesis and chemical industry. With oxygen or air as terminal oxidant, aerobic oxidation catalysis provides the most sustainable and economic oxidation processes. Most aerobic oxidation catalysis employs redox metal as its active center. While nature provides non-redox metal strategy as in pyrroloquinoline quinone (PQQ)-dependent methanol dehydrogenases (MDH), such an effective chemical version is unknown. Inspired by the recently discov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Recently, Luo et al have reported in their preprint that a semiquinone anionic radical species forms upon coordination of LaI 3 with the ortho-quinone o-Q in acetonitrile. [10] An EPR spectrum of the system showed the presence of an organic radical species with g = 2.003, which could not be observed in absence of the metal salt. Furthermore the emergence of traces of radicals when PQQ and lanthanide salts are combined has been observed previously by Daumann and co-workers (see note in the Supporting Information).…”
Section: Epr Investigationmentioning
confidence: 91%
See 2 more Smart Citations
“…Recently, Luo et al have reported in their preprint that a semiquinone anionic radical species forms upon coordination of LaI 3 with the ortho-quinone o-Q in acetonitrile. [10] An EPR spectrum of the system showed the presence of an organic radical species with g = 2.003, which could not be observed in absence of the metal salt. Furthermore the emergence of traces of radicals when PQQ and lanthanide salts are combined has been observed previously by Daumann and co-workers (see note in the Supporting Information).…”
Section: Epr Investigationmentioning
confidence: 91%
“…Recently Luo et al showed that the semiquinone-lanthanum complex [La(o-Q * À ) 2 ] can also serve as an efficient catalyst for the oxidation of alcohols under aerobic conditions. [10] The catalysis was initialized by reduction through single electron transfer of the ortho-quinone ligand o-Q after coordinating with LaI 3 . A screening of different conditions showed that the addition of a base did not have an obvious effect on the reaction outcome.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Luo et al have reported in their preprint that a semi-quinone anionic radical species forms upon coordination of LaI3 with the ortho-quinone o-Q in acetonitrile. [12] An EPR spectrum of the system showed the presence of an organic radical species with g = 2.003, which could not be observed in absence of the metal salt. Furthermore the emergence of traces of radicals when PQQ and lanthanide salts are combined has been observed previously by Daumann and coworkers (see note in SI there).…”
Section: Epr Investigationmentioning
confidence: 91%
“…Recently Luo et al showed that the semiquinone-lanthanum complex [La(o-Q -• )2] can also serve as an efficient catalyst for the oxidation of alcohols under aerobic conditions. [12] The catalysis was initialized by reduction via single electron transfer of the ortho-quinone ligand o-Q after coordinating with LaI3. A screening of different conditions showed that the addition of a base did not have an obvious effect on the reaction outcome.…”
Section: Introductionmentioning
confidence: 99%